Preparation and optimization of poly (lactic-co-glycolic acid) rod-shaped particles in nano size range for paclitaxel delivery - Xu, Mengyao; Liao, Zuyue; Liu, Yang; Guo, Shiwei; Hu, Haiyang; Chen, Tao; Wu, Yuesong; Wan, Shengli; Zhou, Meiling; Lu, Muhe; Jiluo, Shiluo; Yao, Lan; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Nanoparticle shape has been acknowledged as an important design parameter due to its influence on nanoparticle interaction with biological systems. However, there is lacking of simple and scalable preparation technique for drug loaded non-spherical polymeric nanoparticles for a long time, thus hindering the potential applications. Although our previous research has modified the traditional emulsion solvent evaporation technique by adding guest molecules to prepare non-spherical poly (lactic-co-glycolic acid) (PLGA) particles, it is difficult to obtain nano-sized rods with minor axis less than 200 nm, which may have great potential in cancer therapy. Herein, in present research, the two-step ESE method was used and optimized to prepare PLGA nanorods for paclitaxel delivery. Firstly, the single-factor experiment was used to screen the influence of multi-factors of type of guest molecules, concentration of guest molecules, emulsification method, surfactant concentration, oil volume, PLGA concentration on the size and shape to determine the range of variables; based on the above range, a multi-factor and multi-level orthogonal experiment was designed. The optimal formula is evaluated by the rod fabrication yield and the aspect ratio of major axis to minor axis. The results showed that the yield of nanorods in the optimal formula was 99% and the aspect ratio was 5.35 ± 2.05 with the minor axis of 135.49 ± 72.66 nm, and major axis of 657.77 ± 307.63 nm. In addition, the anti-cancer drug paclitaxel was successfully encapsulated in PLGA nanorods by the same technique. Our results not only enrich the ESE technique for preparing small sized PLGA nanorods, but also envision the potential application of nanorods for targeted cancer therapy with the delivery of paclitaxel.